Serrated polyps detected during screening colonoscopies - Świątkowski, Maciej; Meder, Agnieszka; Sobczyński, Lesław; Koza, Jarosław; Szamocka, Małgorzata; Brudny, Janina; Korenkiewicz, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : It is estimated that between 15% and 35% of sporadic colorectal cancers (CRC) developing from adenomas come from serrated polyps. Currently, the most effective method used to prevent CRC is the removal of adenomas, including serrated polyps, during colonoscopy. The aim of this paper is to analyze the changes characterized as serrated polyps and detected during screening colonoscopies performed as part of the Screening Program for Early Colorectal Cancer Detection (SPED). Material and methods: In our center, as part of the nationwide SPED between 2000 and 2009, 1,442 screening colonoscopies were performed. Results: Serrated polyps were found in 11.9% of all patients and in 45.8% of patients who had polyps removed by endoscopy. In screening colonoscopy of the large intestine, the following polyps were found most frequently: hyperplastic, < 1 cm, without a stalk, multiple, located in the distal part of the large intestine, in men and in patients with a first-degree relative with a history of abdominal cancer. Detecting and removing polyps was facilitated by the fact that the cecum was intubated and the bowel preparation had been performed either very well or well. The detection rate of serrated polyps was not influenced by patients’ place of residence or their age. Conclusions : Serrated polyps constitute a frequent, and very frequent among removed polyps, abnormality detected during screening colonoscopy.